Antigen Detection in Urine for Noninvasive Diagnosis and Treatment Monitoring of Visceral Leishmaniasis in Human Immunodeficiency Virus Coinfected Patients: An Exploratory Analysis from Ethiopia - Vogt, Florian (Am J Trop Med Hyg, 2018)
Diagnosis of visceral leishmaniasis (VL) and assessment of treatment response in human immunodeficiency virus (HIV)–coinfected patients still relies on invasive tissue aspiration. This hampers scale-up and decentralization of care in resource-limited settings. Noninvasive diagnostics are urgently needed. KATEX is a frequently used latex agglutination test for Leishmania antigen in urine that has never been evaluated in HIV-coinfected individuals from Leishmania donovani–endemic areas. This was an exploratory sub-study embedded within the screening phase of a trial in highly endemic northwestern Ethiopia. All patients were HIV-positive and aspirate-confirmed VL cases. We assessed diagnostic accuracy of KATEX for VL diagnosis and as test of cure at end of treatment, using tissue aspirate parasite load as reference methods. We also described the evolution of weekly antigen levels during treatment. Most of the 87 included patients were male (84, 97%), young (median age 31 years), and had poor immune status (median cluster of differentiation type 4 count 56 cells/μL). KATEX had moderate sensitivity (84%) for VL diagnosis. KATEX had moderate sensitivity (82%) and a moderate negative predictive value (87%) but only low specificity (49%) and a low positive predictive value (40%) for the assessment of treatment outcomes. Weekly antigen levels showed characteristic patterns during treatment of patients with different initial parasite loads and treatment outcomes. Antigen detection in urine using KATEX can contribute to improved VL diagnosis in HIV-coinfected patients but has limited use for monitoring of treatment response. Better noninvasive diagnostics are needed to reduce reliance on invasive methods and thus to expand and improve clinical care for VL in resource-limited settings.